Cover cropping in a sloping, non-irrigated vineyard: 2 - effects on vegetative growth , yield, berry and wine quality of Cabernet Sauvignon grapes - Monteiro, Ana (2008)
Grapevine vegetative growth, yield, fruit composition and wine quality were studied in the Estremadura Winegrowing Region of Portugal in a ‘Cabernet Sauvignon’ slopping non-irrigated vineyard. During three seasons three treatments were compared: soil tillage (control), permanent resident vegetation, and permanent sown cover crop. When compared to soil tillage, the inter-row sward treatments displayed a lower predawn leaf water potential from bloom to mid-ripening. These differences in vine water status did not affect vine yield or berry sugar accumulation; however, in the third season after experiment setup it induced a significant reduction in vegetative growth in the sward treatments, compared to soil tillage. This vegetative growth reduction had a positive effect on grape composition by reducing titratable acidity and increasing berry skin total phenols and anthocyanins. Those differences were also detected in the wines by the judges who gave a better classification to the wines from the sward treatments. Our results indicate that cover cropping can be a valuable tool for controlling vigour and enhancing wine quality in this winegrowing region.